3p+7=-(p-4)

Simple and best practice solution for 3p+7=-(p-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+7=-(p-4) equation:


Simplifying
3p + 7 = -1(p + -4)

Reorder the terms:
7 + 3p = -1(p + -4)

Reorder the terms:
7 + 3p = -1(-4 + p)
7 + 3p = (-4 * -1 + p * -1)
7 + 3p = (4 + -1p)

Solving
7 + 3p = 4 + -1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add 'p' to each side of the equation.
7 + 3p + p = 4 + -1p + p

Combine like terms: 3p + p = 4p
7 + 4p = 4 + -1p + p

Combine like terms: -1p + p = 0
7 + 4p = 4 + 0
7 + 4p = 4

Add '-7' to each side of the equation.
7 + -7 + 4p = 4 + -7

Combine like terms: 7 + -7 = 0
0 + 4p = 4 + -7
4p = 4 + -7

Combine like terms: 4 + -7 = -3
4p = -3

Divide each side by '4'.
p = -0.75

Simplifying
p = -0.75

See similar equations:

| -90=5(2-5p) | | .05((1-x^6)/(1-x))=100 | | 24uv^4w^7-28u^4v^8=0 | | (1/6,-2) | | (3m+2n-7p)=-6m^3np^3-4m^2n^2p^3+14m^2np^4 | | 6x^3=729 | | 2(x+4)-2=4(x+2)-6 | | 50x^2-5x-3= | | 18x-3x=10 | | -10(s+1)=-71 | | 2/3a-4=4 | | 7c+2=5c-10 | | (x+2y)+(2x-3y)i+4i=5 | | (2x^2-3x+6)=-8x^3-24x^2 | | 3x=ax+1 | | (x+2)+(2x-3y)i+4i=5 | | 4/5f=2/3 | | 6(3s+4)=96 | | (2x+3(x-7))=0 | | 0.25e=8 | | 5(a-6)=75 | | -2(z+4)=44 | | (u-6)*10=100whatisu | | -4q-8=16 | | 5x^8+35x^7+60x^6= | | 10t-20=60 | | (8a-7b)=16a^2b-14ab^2 | | 10+-20=60 | | N-41=20+4 | | -4(c+1)+2c=3(2b-1) | | 4(4y+5)=60+5(y+3) | | x^5-x^4-5x^3-x^2+8x-4=0 |

Equations solver categories